Associations of clinicopathological factors with local treatment and survival outcome in elderly patients with ductal carcinoma in situ - Zhang, Xu; Zeng, Yufei; Wang, Zheng; Chen, Xiaosong; Shen, Kunwei (Frontiers in Surgery, 2023)
Background: Local treatment for ductal carcinoma in situ (DCIS) remains controversial for elderly patients. This study aims to evaluate the association of local treatment, clinicopathological factors, and survival in elderly DCIS patients. Methods: Patients ≥ 60 years diagnosed with DCIS from January 2009 to December 2018 were retrospectively included. Local treatment including breast surgery, axillary lymph node (ALN) surgery, and radiotherapy were analyzed among subgroups (age of 60-69, 70-79, and ≥ 80 years), and their associations with clinicopathological features and prognostic outcome were further evaluated. Results: A total of 331 patients were included. Eventually 86 patients received breast conserving surgery (BCS) and 245 patients received mastectomy. ALN surgery was omitted in 62 patients. Age and tumor size were independent factors that influenced the breast and ALN surgery (P<0.05). Compared with patients aging 60-69, patients ≥ 80 years were more likely to receive BCS (OR 4.28, 95% CI 1.33-13.78, P=0.015) and be exempt from ALN surgery (OR 0.19, 95% CI 0.05-0.69, P=0.011). Patients with tumor >1.5cm were significantly less likely to receive BCS (OR 0.45, 95%CI 0.25-0.83, P=0.011) and more likely to receive ALN surgery (OR 4.41, 95%CI 1.96-10.48, P=0.001) compared to patients with tumor ≤ 1.5cm. Postoperative radiotherapy was performed in 48.8% patients who received BCS. Age was the only factor that associated with the radiotherapy decision after BCS in elderly DCIS patients (P=0.025). No significant recurrence-free survival difference was observed among patients receiving different local treatments. Conclusions: Age was related to the choice of local treatment in elderly DCIS patients, but different treatment patterns didn’t impact disease outcome.